2021
DOI: 10.3390/su13020647
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Urban Spatial Patterns and Functional Zones Using Sina Weibo POI Data: A Case Study of Beijing

Abstract: With the development of Web2.0 and mobile Internet, urban residents, a new type of “sensor”, provide us with massive amounts of volunteered geographic information (VGI). Quantifying the spatial patterns of VGI plays an increasingly important role in the understanding and development of urban spatial functions. Using VGI and social media activity data, this article developed a method to automatically extract and identify urban spatial patterns and functional zones. The method is put forward based on the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 27 publications
0
35
0
4
Order By: Relevance
“…The auxiliary data from various sources can be combined for gridded population mapping via machine learning regression. It was demonstrated that location-based services (LBS) data, derived from mobile phones, Baidu map, Tencent LBS, Sina Weibo, and so on, offer the possibility of illustrating gridded population maps more accurately and finely in urban areas [11,22,[64][65][66][67][68][69][70][71]. In particular, the accuracy of gridded population maps can be improved significantly through the integration of remote sensing data and LBS data [72].…”
Section: Principal Findings and Meaningful Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The auxiliary data from various sources can be combined for gridded population mapping via machine learning regression. It was demonstrated that location-based services (LBS) data, derived from mobile phones, Baidu map, Tencent LBS, Sina Weibo, and so on, offer the possibility of illustrating gridded population maps more accurately and finely in urban areas [11,22,[64][65][66][67][68][69][70][71]. In particular, the accuracy of gridded population maps can be improved significantly through the integration of remote sensing data and LBS data [72].…”
Section: Principal Findings and Meaningful Implicationmentioning
confidence: 99%
“…Second, the data sources for prompting the fine-scale spatial decomposition research need to be enriched. Dynamic geo-data, such as mobile phone communication data [74], social media check-in data [64,67,68], GPS trajectory data [66], and so on, can effectively improve the accuracy of the proposed approach and provide the spatial-temporal information on population distribution on the fine scale, which is very important for issues in urban governance, such as emergency management, public service facility configuration, and so on. In future research, we could focus on revealing the spatial-temporal dynamics of population distribution with more individual-scale trajectory data, such as mobile phone signaling data, non-floating bicycle trajectory data, online car trip hailing data, and so on.…”
Section: Explanations For Further Researchmentioning
confidence: 99%
“…Weibo tweets have been utilized with their geographic and semantic information, wherein the text has been widely used in analyzing public opinion [16], user behavior [17], subjective wellbeing [18], climate change [19], and hazard management [20]. The geotags have been used as an important open data for identifying land use [21], urban function area [22,23], urban spatial structure [24], and delimitating urban boundaries [25]. Recent studies also extract human mobility information based on geotags to analyze regional spatial networks [26] and evaluate spatial segregation patterns [27].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods have relied on field surveys and remote-sensing images [12,13]. However, crowdsourced geographic information (e.g., point-of-interest, mobile, and traffic-flow data) provides a new channel for describing and understanding urban spatial structures [4,[14][15][16][17][18][19][20][21]. Combining these two types of methods can make the identification of urban functional areas more accurate [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Related studies have typically focused on economically developed cities, such as Beijing [19,26,27,37], Shenzhen [25,36,38], Guangzhou [14,39], Wuxi [40], and New York [41]. While Klapka and Halás [17,42] studied urban functional zones in the Czech Republic, few studies have focused on old industrial cities (except for Wuhan [20]) and Rust Belt cities.…”
Section: Introductionmentioning
confidence: 99%